Mixed Convection Heat Transfer of a Non-Newtonian Power-Law Fluid over a Vertical Wavy Surface with Internal Heat Generation or Absorption - Abdolmaleki, Eisa; Saberi Najafi, Hashem (Mechanical Technology and Engineering Insights, 2025)
In the present study, combined convection heat transfer in the boundary layer flow of a non-Newtonian fluid with internal heat generation or absorption over a vertical wavy surface is investigated. A coordinate transformation is employed to convert the governing equations from the wavy geometry to an equivalent flat surface. The transformed boundary layer equations are solved numerically using the finite difference method. The effects of key parameters, including the heat generation/absorption parameter, wave amplitude, generalized Prandtl number, and power-law viscosity index, are examined through variations of the local and average Nusselt numbers as well as the skin friction coefficient. The results indicate that increasing the heat generation parameter leads to fluid heating and a corresponding reduction in the heat transfer rate in non-Newtonian fluids.